2018
DOI: 10.14254/2071-8330.2018/11-1/22
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of GDP and its impact on the pharmaceutical sector of Ecuador (2007-2016)

Abstract: In the last decade there has been an increase in Ecuador's GDP observed, despite the economic slowdown in 2015 and 2016. Likewise, there has been an increase in spending on health, especially in the public sector, supported by the legislative framework of Ecuador. The objective of the article is to determine the relationship between GDP and healthcare expenditures, both public and private, and also the the income and profits of the pharmaceutical industry. In addition, we intends to check whether the changes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Using the forecast error variance, impulse–response functions and historical decomposition, the study found that exchange rate, money supply, inflation rate, interest rate, GDP and health-care costs have a significant impact on the market capitalization and stock prices of the pharmaceutical industry. Similarly, Pérez et al (2018) used regression analysis and the Pearson correlation coefficient to investigate how the pharmaceutical industry’s financial performance in Ecuador relates to GDP and health-care spending. The study found the correlation between rising incomes and increased health-care expenditures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the forecast error variance, impulse–response functions and historical decomposition, the study found that exchange rate, money supply, inflation rate, interest rate, GDP and health-care costs have a significant impact on the market capitalization and stock prices of the pharmaceutical industry. Similarly, Pérez et al (2018) used regression analysis and the Pearson correlation coefficient to investigate how the pharmaceutical industry’s financial performance in Ecuador relates to GDP and health-care spending. The study found the correlation between rising incomes and increased health-care expenditures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Measuring and quantifying the level of health and wellbeing within countries is a long-term subject of research of many research teams, economists, and international institutions ( 1 6 ). Many authors point to procedural and methodological difficulties of these measurements ( 7 – 9 ). Similarly, knowledge of countries' health systems and their determinants is a very important aspect in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Although pharmaceutical expenditure in the most OECD countries covers spending on prescription and over-the-counter medicines consumed as outpatient treatment [ 8 ], pharmaceutical expenditure in Iran is included pharmaceutical spending on outpatient and inpatient medicines. Empirical studies have shown that there is a strong relationship between GDP and pharmaceutical sector profits and health expenditure in general [ 19 ]. On the other hand, health expenditure and GDP have a reciprocal relationship in each country.…”
Section: Introductionmentioning
confidence: 99%